THE IMPLEMENTATION OF TRAINING IN FAMILY INCOME INCREASING BUSINESS PROGRAM CASE STUDY IN PENDRIKAN LOR VILLAGE SEMARANG CITY 2017 - Mohammad Soko Marhendi; Indra Lestari Fawzi (Politeknik Kesejahteraan Sosial Bandung, 2019)
Until now poverty still exists and is found in people in Java. Central Java is the province with the largest poverty depth index in Java. For this reason, sustainable empowerment needs to be sought and used to overcome the problem of poverty. One of the empowerment programs carried out by the regional government is the Family Income Improvement Business Program (UP2K). This study uses a qualitative approach that aims to describe the empowerment process that has been carried out especially at the stage of the training program. The type of research is descriptive. The results obtained in the training research were carried out by determining training needs, designing training programs, and evaluating program effectiveness. If this stage is carried out it will have a positive impact on the family's economic capacity. The driving factors of the implementation of the training include adaptive and competent trainers and supporting facilities and infrastructure. However, in the implementation, there were still obstacles in the field, including low education of participants and the timing of training which often clashed with the participants’ activities. The suggested solution is to use competent trainers and socialize before training.